Hydrometeorological Factors Influencing Breakup Ice Jam Occurrence at Fort McMurray, Alberta: Supplementary Files ... - Robichaud, Claudine (University of Alberta Library, 2003)
River ice jams are commonly observed on the Athabasca River in the vicinity of Fort McMurray, Alberta. These natural events have been responsible for serious flood damages at the city of Fort McMurray. No method is currently in use to predict the occurrence or severity of ice jams at this site. A meteorological and hydraulic database was compiled in this research in order to investigate which factors influence the nature and rate of river ice breakup at Fort McMurray. These factors were first studied separately with simple threshold models. The results demonstrated that ice jams formation at Fort McMurray is very complex since none of the factors investigated individually provided any information on the occurrence of ice jams at the studied site. Linear and multiple linear regression models were also studied. Promising results were obtained when multiple factors were used to predict breakup flood levels. ...